Productos De Gran Rentabilidad En El Banco Scotiabank Colpatria (2022)
The proposal to be carried out is an internship job for the company Scotiabank Colpatria and the Antonio Nariño University, in order to obtain the respective qualification in the degree option that I must present as a requirement in my economics career, which will take place from the month of August of the year 2021 until the month of November of the same year. This internship was endorsed at the branch of the Santafé Shopping Center in the city of Bogotá, specifically in the commercial area, from which the initial work was to carry out the tasks set by the branch leader, in this case the manager, with whom it was planned and led a plan of strategies and new methods of tools that allow to increase placement of your most profitable products, this in order to increase your commissions and close the gaps of goals not achieved in previous months. Day by day, new ideas and strategies were worked on with the different collaborators and sought ways to generate more knowledge that would allow good advice and a better focus on the market, an objective that the branch and the bank in general must have, moment of capturing new resources or the placement of credit products.